Effectiveness of Progressive Muscle Relaxation as an Effort to Reduce Anxiety in Asthma Patients in Emergency Departments: Implications for Health Policy and Nursing Practice - Maria Kurni Menga; Lenny Gannika (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Anxiety is a common and clinically significant comorbidity among asthma patients in emergency departments (EDs), potentially worsening respiratory symptoms and complicating management. Non-pharmacological interventions such as Progressive Muscle Relaxation (PMR) remain underutilized in acute care. This study aimed to evaluate the effectiveness of PMR in reducing anxiety among asthma patients in ED settings. Methods: A quasi-experimental pretest–posttest control group design was employed. The study included 70 adult asthma patients (35 intervention, 35 control) recruited using purposive sampling in an ED setting over three months. The intervention group received a structured 15-minute PMR session in addition to standard care, while the control group received standard care only. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI). Data were analyzed using paired and independent t-tests, followed by multivariate linear regression to control for potential confounders. Results: The intervention group demonstrated a significantly greater reduction in anxiety scores compared to the control group (mean difference: -14.2 vs -4.4; p < 0.001). Multivariate analysis confirmed that PMR was an independent predictor of anxiety reduction (β = -9.85; 95% CI: -12.40 to -7.30; p < 0.001), after adjusting for age, sex, and asthma severity. Asthma severity was also significantly associated with anxiety levels (β = 1.75; 95% CI: 0.30 to 3.20; p = 0.018). Conclusion: PMR is an effective, low-cost, and feasible intervention for reducing anxiety among asthma patients in ED settings. Integrating PMR into emergency nursing protocols may enhance patient-centered care and improve clinical outcomes. Policymakers should consider incorporating non-pharmacological interventions into acute care guidelines to support holistic and sustainable health service delivery.